APPLICATION OF WATER QUALITY AND ECOLOGY INDICES OF BENTHIC MACROINVERTEBRATE TO EVALUATE WATER QUALITY OF TERTIARY IRRIGATION IN MALANG DISTRICT - Kartikasari, Desi (Journal of Tropical Life Science, 2013)
This research aims to determine the water quality of tertiary irrigation in several subdistricts in Malang, namely Kepanjen, Karangploso, and Tumpang. The water quality depends on the water quality indices (National Sanitation Foundations-NSF Indices and OConnors Indices based on variables TSS, TDS, pH, DO, and Nitrate concentrate) and ecological indices of benthic macroinvertebrate (Diversity Indices Shannon-Wiener, Hilsenhof Biotic Indices-HBI, Average Score per Taxon-ASPT which is calculated by Biological Monitoring Working Party-BMWP, Ephemeroptera Indices, Plecoptera, Trichoptera-EPT). Observation of the physico-chemical water quality and benthic macroinvertebrate on May 2012 to April 2013. The sampling in each subdistrict was done at two selected stations in tertiary irrigation channel with three plot at each station. The data of physico-chemical quality of water were used to calculate the water quality indices, while the benthic macroinvertebrate data were used to calculate the ecological indices.The research findings showed that 27 taxa of benthic macroinvertebrates belong 10 classes were found in the three subdistrict. The pH, DO, Nitrate, TSS and TDS in six tertiary irrigation channels in Malang still met the water quality standards based on Government Regulation No.82 of 2001 on Management of Water Quality and Water Pollution Control Class III. Based on NSF-WQI indices and O'Connor's Indices, water qualities in these irrigation channels were categorized into medium or moderate (yellow) to good (green) category. However, based on benthic macroinvertebrate communities which was used to determine the HBI, the water quality in the irrigation channels were categorized into the air category (fairly significant organic pollution) to fairly poor (significant organic pollution), while based on the value of ASPT, the water were categorized into probable moderate pollution to probable severe pollution. The irrigation water which was categorized into good by WQI was consistently included into fair based on HBI and probable moderate pollution based on ASPT. Key words: ecological index, water quality index, benthic macroinvertebrate, Malang irrigation channel